2021
DOI: 10.1186/s12873-021-00429-z
|View full text |Cite
|
Sign up to set email alerts
|

A two-year review of adult emergency department mortality at Tikur Anbesa specialized tertiary hospital, Addis Ababa, Ethiopia

Abstract: Background Adult emergency department mortality remains high in resource-limited lower-income countries. The majority of deaths occur within the first 24 h of presentation to the emergency department. Many of these mortality’s can be alleviated with appropriate interventions. This study was aimed to assess the magnitude, cause, and factors related to very early mortality in patients presented to the emergency department of Tikur Anbesa Specialized Tertiary Hospital, Ethiopia from March 2018 to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…However, the mortality rate in our ED was higher compared to those found in high-income countries 0.1% in France [ 8 ]. We also found that males had relatively higher mortality rate than females at the ED (ratio = 1.2:1) and it is supported by multiple previous studies (1.2:1 [ 11 ]; 1.4:1 [ 13 ]; 1.3:1 [ 10 ]; 1.3:1 [ 12 ]). This could be due to higher exposure of males to situations that might lead to emergency conditions such as trauma [ 13 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the mortality rate in our ED was higher compared to those found in high-income countries 0.1% in France [ 8 ]. We also found that males had relatively higher mortality rate than females at the ED (ratio = 1.2:1) and it is supported by multiple previous studies (1.2:1 [ 11 ]; 1.4:1 [ 13 ]; 1.3:1 [ 10 ]; 1.3:1 [ 12 ]). This could be due to higher exposure of males to situations that might lead to emergency conditions such as trauma [ 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…This mortality rate is comparable to previously reported rates in low- and middle-income countries [ 10 , 13 ]. However, higher mortality rates were also reported by previous studies which counted death on arrival as an ED death [ 11 , 12 ]. In our study, we included only patients who had signs of life during arrival at the ED and died later.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In contrast, it could also be that the Tanzanian cohort of ED patients spent less time in the ED compared to those in this study seeing as to how the mortality rate rose to 14 times the initial for the overall study after leaving the ED [2] . Mortality in ED has been reported to be at least five times higher in SSA [19] and patient delays in the ED and suboptimal infrastructure contribute to high mortality…”
Section: Discussionmentioning
confidence: 99%